Hubungan Antara Pengetahuan dan Pekerjaan Terhadap Nyeri yang Ditimbulkan oleh Penyakit Arthritis Rheumatoid di Puskesmas Sungai Lumpur: Penelitian - Sherly Widianti; Musmulyadi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Rheumatoid arthritis is a chronic autoimmune disease that attacks the joints and often causes persistent pain. This pain can interfere with daily activities and reduce the quality of life of patients. The level of knowledge and type of occupation are thought to play a role in the perception and intensity of pain experienced. This study aimed to analyze the relationship between knowledge level and type of occupation with pain frequency among rheumatoid arthritis patients in the working area of Sungai Lumpur Public Health Center, Cengal Subdistrict, Ogan Komering Ilir Regency. The research design was analytic quantitative with a cross-sectional approach. A total sampling technique was applied, consisting of 44 respondents. Data were analyzed using the chi-square test to examine the relationship between variables. The majority of respondents had a low level of knowledge (59.1%) and worked as fishermen (68.2%). As many as 90.9% of respondents reported frequent pain. Bivariate analysis showed a significant relationship between knowledge level and pain frequency (ρ = 0.001), as well as between type of occupation and pain frequency (ρ = 0.003). The study concluded that there is a significant relationship between knowledge level and type of occupation with pain intensity in rheumatoid arthritis patients.